CRISPR-Cas12a/Aurora Deoxyribozyme Cascade: A Label-Free Ultrasensitive Platform for Rapid Salmonella Detection - Cong Shi; Huimin Tan; Zhou Yu; Weilin Li; Yan Man; Qinghai Zhang (Foods)
The rapid and ultrasensitive detection of Salmonella holds strategic significance for food safety surveillance and public health protection systems. This study innovatively developed a label-free biosensing platform based on the synergistic integration of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-Cas12a and the fluorescent deoxyribozyme Aurora for the efficient detection of foodborne Salmonella. The detection mechanism operates through a molecular cascade reaction: target-activated Cas12a protein specifically degrades Aurora deoxyribozyme via its trans-cleavage activity, thereby abolishing the enzyme’s catalytic capability to convert 4-methylumbelliferyl phosphate (4-MUP) into the highly fluorescent product 4-methylumbelliferone (4-MU). This cascade ultimately enables quantitative target analysis through fluorescence signal attenuation. Following systematic optimization of critical reaction parameters, the biosensing system demonstrated exceptional analytical performance: a detection limit of 1.29 CFU/mL with excellent linearity (R2 = 0.992) spanning six orders of magnitude (1.65 × 101–106 CFU/mL), along with high specificity against multiple interfering bacterial strains. Spike-and-recovery tests in complex food matrices (milk, chicken, and lettuce) yielded recoveries of 90.91–99.40% (RSD = 3.55–4.72%), confirming robust practical applicability. Notably, the platform design allows flexible detection of other pathogens through simple replacement of CRISPR guide sequences.